Odpowiedzi

2010-03-11T18:23:29+01:00
-10=4-2x
2x=4+10
2x=14/:2
x=7

17=-6+3x
17+6=3x
23=3x/:3
7⅔=3

-3=-6x+10
6x=10+3
6x=13 /:6
x=2 i 1/6

-15=3x-10
-15+10=3x
-5=3x /:3
-5/3=x

-16=-4x-7
4x=-7+16
4x=9 /:4
x=2,25
1 5 1
2010-03-11T18:25:24+01:00
-10=4-2x
2x = 4 + 10
2x = 14 ÷ 2
x = 7

17=-6+3x
-3x = -6 - 17
-3x = -23 ÷ (-3)
x = 7 2/3 (dwie trzecie)


-3=-6x+10
6x = 10 + 3
6x = 13 ÷ 6
x = 2 1/3 (jedna trzecia)

-15=3x-10
-3x = -10 + 15
-3x = 5 ÷ (-3)
x = -5/3 = -1 2/3 (dwie trzecie)

-16=-4x-7
4x = -7 + 16
4x = 9 ÷ 4
x = 9/4 = 2 1/4 (jedna czwarta)
1 5 1
2010-03-11T18:29:30+01:00
-10=4-2x
2x=10+4
2x=14/:2
x=7


17= -6+3x
-3x= -6-17
-3x= -23/ :(-3)
x=7(6)


-3=6x+10
-6x=10=3
-6x=13/: (-6)
x=-2(1)


-15=3x-10
-3x= -10=5
-3x=5/:(-3)
x= -1(2)



-16=-4x-7
4x=-7=16
4x=9 2,5
1 5 1